FOOD SAFETY MANAGEMENT IN METROPOLITAN LIMA, PERU, FROM 2010 TO 2024 - Fano Castro, Paola (2025)
The objective of this study was to evaluate the influence of the integration of management processes among different sanitary authorities on food safety in Lima, during the period 2010–2024. Surveys were conducted with a sample of 90 public officials, divided among DIGESA, SENASA, and SANIPES, representing three sanitary authorities. The findings indicate that food safety management is insufficient, mainly due to poor risk assessment by the public sector and inadequate implementation of existing regulations. A lack of appropriate allocation of financial and human resources to the sanitary authorities was identified, along with limited consumer awareness regarding the importance of food safety. These factors have led to the ineffective implementation of a food safety management system. Among the most notable findings, only 4% of food manufacturing establishments possess all required sanitary authorizations. Pesticide levels in fruit and vegetable products reach 29.5%, while in meat products they reach 10%. The prevalence of heavy metals in fruit and vegetable products is 18%, and 10% in meat products. An average of 10 cases of Foodborne Diseases (FBD) per year has been reported over the past 14 years. These findings highlight significant shortcomings in the surveillance and monitoring of food safety by sanitary authorities. Keywords: food safety, FBD, public health, DIGESA, SENASA, SANIPES, quality.